Hybrid meat products and co-creation: What do consumers say, feel and think? - Ryder, Chris; Jaworska, Sylvia; Grasso, Simona (Frontiers in Nutrition, 2023)
What consumers say about food and what kind of words they use to do so offers direct insights into their perceptions, preferences, reasoning and emotions. This study explores evaluations of hybrid meat products of some 2,405 consumers from three countries, England (802), Denmark (802) and Spain (801). As part of a large survey, consumers were prompted to note down 4 words that come to mind when they read a description of a hybrid meat product, and then again after they were involved in a hypothetical co-creation task of a hybrid meat product. The language material (18,697 words and phrases in total) was processed using computational corpus-based analysis and manual classification into semantic categories including: Evaluation (positive, negative or neutral), Sensory, Production, Emotion, Diets, Quality, Ethics and Other. The analysis suggests that consumers consider many dimensions when it comes to the evaluation of hybrid meat products including ethical conduct and sustainability. For all three languages, the number of positive words increased and the number of negative words decreased significantly (p<0.001) following the co-creation task, suggesting that consumers see such products very positively once they are more familiar with them and know more about the ingredients. Subcategories that received most words include: taste, ingredients, healthiness, naturalness, innovation and environment implying that these areas are of most importance when it comes to the evaluation of hybrid meat products. The concept of nutrition (especially words pointing to positive aspects such as ‘rich in vitamins’, ‘nutritious’) also rose significantly in use after co-creation. The study reveals consumers’ vocabulary of hybrid meat products across the three countries and offers important insights for food producers to help them create innovative products that better align with consumers’ perceptions and expectations.